2000
DOI: 10.1902/jop.2000.71.8.1278
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Fetal Enamel Matrix Derivative Enhances Bone Formation Induced by Demineralized Freeze Dried Bone Allograft In Vivo

Abstract: EMD is not osteoinductive. However, it is osteopromotive, due in part to its osteoconductive properties, but a threshold concentration is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
133
1
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(144 citation statements)
references
References 38 publications
9
133
1
1
Order By: Relevance
“…DEXA method may be used to measure tooth mineral density (TMD) at the particular region of interest (ROI) of sample or for the whole sample. The results of measurements are given in mineral density expressed as g/ cm 2 . Apart from the TMD, DEXA allows the measurement of tooth mineral content (TMC), which is expressed in grams.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DEXA method may be used to measure tooth mineral density (TMD) at the particular region of interest (ROI) of sample or for the whole sample. The results of measurements are given in mineral density expressed as g/ cm 2 . Apart from the TMD, DEXA allows the measurement of tooth mineral content (TMC), which is expressed in grams.…”
Section: Discussionmentioning
confidence: 99%
“…Swine teeth possess mineralization pattern of enamel comparable to that of humans [6]. It is considered that composition of swine enamel is similar to human enamel [2,20]. Experimental studies on skeletal system have also confirmed similarities between bone growth plate structure and mineralization process in humans and pigs [27].…”
mentioning
confidence: 85%
“…The specific characteristic of EMD regarding its bone formation ability (osteoinductive, osteoconductive, or osteogenic) was examined by means of a nude mouse muscle implantation assay (Boyan et al, 2000). No ossicle formation occurred when EMD alone was implanted into cell muscle under conditions that support osteoinduction by demineralized freeze-dried bone allograft (DFDBA).…”
Section: (Ii6) In Vivo Studies (Ii61) In Vivo Animal Studiesmentioning
confidence: 99%
“…This study showed that it is possible to induce regeneration of all the periodontal tissues (acellular cementum, periodontal ligament, and alveolar bone) in a way that mimics the normal development of these tissues. In addition, the periodontal regeneration properties of the enamel matrix were associated with the amelogenin fraction .The specific characteristic of EMD regarding its bone formation ability (osteoinductive, osteoconductive, or osteogenic) was examined by means of a nude mouse muscle implantation assay (Boyan et al, 2000). No ossicle formation occurred when EMD alone was implanted into cell muscle under conditions that support osteoinduction by demineralized freeze-dried bone allograft (DFDBA).…”
mentioning
confidence: 99%
“…Osteoinductivity was assessed with use of a standardized animal model in which demineralized bone matrix is implanted in the gastrocnemius muscle of nude mice and the presence of new bone is determined by quantitative histomorphometry. This assay has been shown previously to be sensitive enough to assess dose-dependent effects of a variety of additives to demineralized bone matrix, as well as differences in demineralized bone matrix donors and variations between bone banks, and the effects of ovariectomy and estrogen replacement therapy [33][34][35][37][38][39][40][41][42][43][44] . Demineralized bone matrix from three or four pairs of donors from each of four different bone banks was used for the study, enabling us to compare the effect of processing methods used, either terminally irradiated or nonirradiated.…”
mentioning
confidence: 99%